Long-term Behavior of Ultra – High Performance Concrete (UHPC) Bended Beams. (2016) - Bărbos, Gheorghe – Alexandru
Abstract: Unlike normal concrete (NC) the behavior of ultra-high performance concrete (UHPC) is different under long-term efforts, if we refer to creep, shrinkage or long-term deflections. It is well known that UHPC has special properties, like compressive strength higher than 150 MPa and tensile strength higher than 20 MPa - in case of UHPC reinforced with steel-fibers (Magureanu, 2010). Nevertheless, UHPC is not so elucidated regarding creep straining or serviceability behavior in case of structural elements. Some studies made on UHPC samples (Flietstra, 2011) (Burkart, 2009) shown that the creep is significantly reduced if the concrete is subjected to heat treatment and if it contains steel-fiber reinforcement. Relating thereto, it is important to know how does structural elements made of this type of concrete works in service life under long-term loadings. The results obtained on UHPC samples, regarding creep straining from tension or compression efforts may not be generalized in case of structural elements (e.g. beams, slabs, columns) subjected to bending (Spasojevic, 2008). Making this study it was proposed to understand the influence of the heat treatment and steel-fiber addition on the rheological phenomena of UHPC bended beams.